2004
DOI: 10.1097/00129492-200411000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Postoperative Relapsing/Residual Cholesteatomas With Diffusion-Weighted Echo-Planar Magnetic Resonance Imaging

Abstract: EPI-DWI may be a useful tool in differentiating between cholesteatomatous and noncholesteatomatous tissues after closed cavity mastoidectomy. Further investigations are, however, required to establish the practical utility of EPI-DWI on larger series as a screening modality in the follow-up after closed cavity mastoidectomies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
68
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 11 publications
4
68
1
2
Order By: Relevance
“…16 Previous studies on the detection of residual cholesteatomas, including those with 17-45 patients, have reported sensitivities varying from 12.5% to 100%, depending on the study. [11][12][13][14] Conversely, the specificity has been more comparable among these studies, ranging from 91% to 100%. In the present study, the sensitivity, specificity, PPV, and NPV were 60%, 72.73%, 80%, and 50%, respectively.…”
Section: Epi Dwi For Residual Cholesteatoma Detectionmentioning
confidence: 81%
See 1 more Smart Citation
“…16 Previous studies on the detection of residual cholesteatomas, including those with 17-45 patients, have reported sensitivities varying from 12.5% to 100%, depending on the study. [11][12][13][14] Conversely, the specificity has been more comparable among these studies, ranging from 91% to 100%. In the present study, the sensitivity, specificity, PPV, and NPV were 60%, 72.73%, 80%, and 50%, respectively.…”
Section: Epi Dwi For Residual Cholesteatoma Detectionmentioning
confidence: 81%
“…[8][9][10] Results of sensitivity, specificity, positive predictive value (PPV), and NPV vary among previous studies. 8,[11][12][13][14][15] One explanation for this discrepancy may be the different sizes of residual cholesteatomas studied in these series.…”
mentioning
confidence: 99%
“…Other studies using diffusion MRI reported high specificity levels in diagnosing cholesteatomas larger than 0.5cm (Table 1) 11,12,15,16 . Vercruysse 16 reported lower sensitivity levels due to increased prevalence of residual cholesteatomas smaller than 0.5cm in size.…”
Section: Discussionmentioning
confidence: 91%
“…Duyarlılık ve özgüllük oranları; Aikele ve ark. nın [1] yaptıkları çalışmada sırasıyla %77 ve %100, Stasolla ve ark.nın [12] yaptıkları çalış-mada %86 ve %100, Jindal ve ark.nın [13] yaptıkları çalışmada %83 ve %82, Vercruysse ve ark.nın [14] yaptıkları çalışmada %12.5 ve %100, Venail ve ark.nın [15] yaptıkları çalışmada ise %60 ve %72 bulunmuştur. Bizim çalışmamızda ise EP-DAG'nin duyarlılık ve özgüllüğü sıra-sıyla %97.6 ve %92 bulundu.…”
Section: şEkil 3 Sol Kulakta Geçirilmiş Masteidektomi Ameliyatı öYküunclassified
“…nın, [1] Vercruysse ve ark.nın, [14] Jindal ve ark. nın, [13] Stasolla ve ark.nın, [12] Venail ve ark.nın [15] yaptıkları çalışmalarda sadece 5 mm'den büyük kolesteatomları göz önünde tutarsak, bu çalışma-larda duyarlılık %100'e ulaşır. Plouin-Gaudan'ın [5] yaptığı 21 hastadan oluşan başka bir çalışmada ise yanlış negatif tanı konulan beş hastanın tamamında kolesteatom boyutu 5 mm'nin altın-da bulunmuştur.…”
Section: şEkil 3 Sol Kulakta Geçirilmiş Masteidektomi Ameliyatı öYküunclassified